Use of preoperative haemostasis and ABO blood typing tests in children: a retrospective observational study using a nationwide claims database in Japan - Hiroshi Yonekura; Kazuki Ide; Yuji Kanazawa; Chikashi Takeda; Yuki Nakamori; Yasunori Matsunari; Michihiro Sakai; Koji Kawakami; Masataka Kamei (BMJ Open)
Objectives To describe the prevalence and factors associated with preoperative haemostasis and ABO blood typing tests for children because these tests might represent low-value care.Design A retrospective observational study.Setting Nationwide insurance claims database in Japan.Participants Patients aged 1–17 years who underwent common non-cardiac surgeries between April 2012 and March 2018 were included. Patients with high-risk comorbidities for bleeding (n=175) and those with multiple eligible surgeries were excluded (n=2121).Main outcome measures We described the proportions of each preoperative test performed within 60 days before an index surgery, including platelet count, prothrombin time (PT), activated partial thromboplastin time (aPTT) and ABO blood typing tests. We also explored the associations between patient-level and institutional-level factors and any preoperative tests, using multilevel logistic regression analysis.Results We included 13 018 patients (median (IQR) age, 5.2 (2.9–7.7) years; 8276 (63.6%) boys) from 1499 institutions. The overall proportion of each test was as follows: platelet count, 78.6%; PT, 54.4%; aPTT, 56.4% and ABO blood typing tests, 50.4%. The proportion of patients undergoing any preoperative tests in the overall sample was 79.3%. Multilevel logistic regression analysis indicated that preoperative tests were associated with type of anaesthesia (general anaesthesia: adjusted OR 7.06; 95% CI 4.94 to 10.11), type of surgery (tonsillectomy: adjusted OR 3.45; 95% CI 2.75 to 4.33) and surgical setting (inpatient procedure: adjusted OR 5.41; 95% CI 3.83 to 7.66). There was one postoperative transfusion event (0.008%) in the entire cohort and 37 postoperative reoperation events for surgical bleeding after tonsillectomy (0.90%).Conclusions In the largest Japanese cohort reported to date, preoperative haemostasis and ABO blood typing tests were performed in a majority of children prior to common paediatric surgeries. Preoperative tests were associated with anaesthesia, surgical type and surgical setting.